Marketing God: A Critical Inquiry into Spirituality in the Workplace - Fred Milacci; Sharon l. Howell (Adult Education Research Conference, 2002)
This paper examines the way spirituality is co-opted and commodified to serve the interests of the marketplace from a faith-based perspective.